Упростите выражения -4(2a2-3b3)2-(3a2+5b3)2

Упростите выражения -4(2a2-3b3)2-(3a2+5b3)2
Гость
Ответ(ы) на вопрос:
Гость
-4(2a²-3b³)²-(3a²+5b³)²=-16a^4+48a²b³-36b^6-9a^4-30a²b³-25b^6= =-25a^4+18a²b³-61b^6
Гость
1) ( 2а^2 - 3b^3 )^2 = 4a^4 - 12a^2b^3 + 9b^6 2) -4( 4a^4 - 12a^2b^3 + 9b^6 ) = - 16a^4 + 48a^2b^3 - 36b^6 3) ( 3a^2 + 5b^3 )^2 = 9a^4 + 30a^2b^3 + 25b^6 4) - 16a^4 + 48a^2b^3 - 36b^6 - ( 9a^4 + 30a^2b^3 + 25b^6 ) = - 16a^4 + 48a^2b^3 - 36b^6 - 9a^4 - 30a^2b^3 - 25b^6 = - 25a^4 + 18a^2b^3 - 61b^6
Не нашли ответ?
Ответить на вопрос
Похожие вопросы